2019
DOI: 10.1016/j.surfcoat.2019.01.071
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion strength of titanium particles to alumina substrates: A combined cold spray and LIPIT study

Abstract: The cold spray process and laser-induced projectile impact test (LIPIT) are used to deposit Ti powder particles on sintered polycrystalline Al2O3. Whereas LIPIT allows real-time observations of single particle impact and measurement of particle impact velocity, cold spray rapidly and simultaneously deposits particles with a wide range of deposition velocities and sizes. By use of these two techniques, the effect of particle velocity and substrate morphology on adhesion strength of single splats is investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…For the IP sprayed at the highest condition, deformation resulting in nearly full closure of all pores was observed. Higher spray conditions might lead to better adhesion, but previous studies by our group have shown that eventually fracture of the alumina occurs leading to a drop in splat adhesion strength [13].…”
Section: Velocitymentioning
confidence: 86%
See 1 more Smart Citation
“…For the IP sprayed at the highest condition, deformation resulting in nearly full closure of all pores was observed. Higher spray conditions might lead to better adhesion, but previous studies by our group have shown that eventually fracture of the alumina occurs leading to a drop in splat adhesion strength [13].…”
Section: Velocitymentioning
confidence: 86%
“…Yet, to date, there is no standardized testing methodology for testing the adhesion of single micron-sized particles. Chromik [12,13,15]. While failure under the applied load is not completely in tension (mode I) or in shear (mode II) as traditional adhesion testing techniques, results from this technique, accompanied by extensive post-test characterization, are useful to characterize the deposition process and bonding mechanism.…”
Section: Methodsmentioning
confidence: 99%
“…The formation of a jet at the interface allows the two interfaces to conform to one another, thereby promoting mechanical interlocking (Ref 18, 66, 91, 92). Since no micro-or macroscale deformation has been reported during impact in the ceramic, mechanical interlocking in metal/ ceramic interfaces is a result of powder material seeping into the cavities on the substrate ( Ref 44,52,53). A roughened ceramic surface, with protrusions and valleys smaller than the particle size, appears to promote deformation.…”
Section: Factors Affecting Adhesionmentioning
confidence: 99%
“…It has important value and application prospects in the field of electronic information industry and national defense and also plays an important role in the development of CM industry. In the metallisation process of CS ceramics, the velocity and temperature of the particles are determined by the process parameters and the deformation behaviour of the particles, and the velocity The bonding mechanism between the malleable feedstocks and brittle ceramic substrates was analysed Atomic mixing and limited amorphisation will be caused by the high-speed collision cascade of particles, thereby enhancing the adhesion of the strong coating Al Ti [118] T gas :450°C, 600°C, 800°C P gas :4.0 MPa Atmosphere: Air…”
Section: Perspectivesmentioning
confidence: 99%